Analisis Kebutuhan Bahan Ajar Matematika Terintegrasi Agama Berbasis AKM - Wildan Hakim (JURNAL PUSAKA, 2021)
Teaching materials for mathematics subjects are still experiencing inadequate material. Especially when mathematics is adopted by institutions such as Islamic boarding schools. Integration between teaching materials and institutional materials is very necessary because the integration process will be very useful in supporting the learning and teaching process with students. This research is an argument for the lack of teaching materials that integrate with religious teaching materials that are often referred to by Islamic boarding schools. The ADDIE model or analyze, design, development, implementation, evaluation is used as a reference for this research to see the extent to which the use of teaching materials before being integrated and after achieving the desired results by educators.